If My Memory Serves Me Well: Investigating My Memory for the Past 24 Years - Storms, Gert (Journal of cognition, 2024)
This paper reports on a study of my autobiographical memory for 2691 notes recorded over 24 years in my diary, without any intention to ever use the notes as test material. I never read any of the notes again until the start of the memory study. I remembered less than two thirds of the recorded events and the retention curve showed a curvilinear shape. I dated 2% of the described events correctly but misdated on average about one and a half year, with an equal number of over and underestimations of the event age. Retention correlated significantly with ratings of salience, emotional involvement, pleasantness, event rehearsal and self-relatedness, but not with intimacy. Dating accuracy correlated with salience, pleasantness, intimacy and event rehearsal, but not with emotional involvement or self-relatedness. Regression analyses showed that event rehearsal was the best predictor of retention and dating, but the predictive value of other ratings was dependent on the content of the recorded events.